Chromogenic and fluorogenic substrates for assaying xylanases of Neurospora - J. H. CHALMERS JR. (Fungal Genetics Reports, 1990)
The Oak Ridge strains of wild type N. crassa grow well with high molecular wight xylan from oat spelts (Sigma X-0376) as the sole carbon source. Xylan, a substituted ß-1,4 linked polymer of xylose, induces high levels of xylanase, xylosidase and ß-galactosidase activities in both culture medium and mycelium. To assay for xylanase activity, chromogenic and fluorogenic substrates have been prepared by procedures based on those of Biely et al. 1985. Anal. Biochem. 144:142-146; Biely et al. 1985. Anal. Biochem. 144:147-151; Rinderknecht et al. 1967. Experientia 23:805; and De Belder and Granath 1973. Carb. Res. 30:375-378. Batches of xylan that have a tan color and granular texture should be dissolved in boiling water, precipitated with two volumes of absolute ethanol, and dried as described below before use. These techniques may also be used to prepare chromogenic and fluorogenic substrates from dextrans, glucans or other high molecular weight polysaccharides to assay endoglycosidases for which suitable assay reagents are not readily available.